2013
DOI: 10.1213/ane.0b013e318273f48e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Levobupivacaine on Wound Healing

Abstract: While levobupivacaine had a positive effect on wound healing during the early period, negative effects were observed thereafter. Additional studies at the molecular level are necessary to determine the cause of these apparently opposite effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
2
24
1
Order By: Relevance
“…Also Nykanen et al concluded that eutectic mixture of lidocaine/prilocaine cream does not affect wound healing adversely and is comparable to 1% lidocaine infiltration in a single blind prospective rat model . Zeren et al reported that levobupivacaine impairs wound healing during the early period and has positive effect during later periods of wound healing . Feder et al showed that lidocaine, bupivacaine and ropivacaine had concentration‐dependent cytotoxic effect on fibroblasts .…”
Section: Discussionsupporting
confidence: 83%
“…Also Nykanen et al concluded that eutectic mixture of lidocaine/prilocaine cream does not affect wound healing adversely and is comparable to 1% lidocaine infiltration in a single blind prospective rat model . Zeren et al reported that levobupivacaine impairs wound healing during the early period and has positive effect during later periods of wound healing . Feder et al showed that lidocaine, bupivacaine and ropivacaine had concentration‐dependent cytotoxic effect on fibroblasts .…”
Section: Discussionsupporting
confidence: 83%
“…It also increased the inflammatory response and collagen synthesis on both the 8 th and 21 st days. [39]…”
Section: Clinical Utilitymentioning
confidence: 99%
“…After the introduction of cocaine to the medical practice, local anaesthetics (LAs) became essential in pain control . LA infiltration along the incision may be used to provide surgical anaesthesia or postoperative analgesia . The most frequently used LAs for these purposes are lidocaine and bupivacaine .…”
Section: Introductionmentioning
confidence: 99%